3rd ICTs and Society Meeting; Paper Session - Inequalities: social, economic, political; Paper 1: Information Society Policies 2.0. A Critical Analysis of the Potential and Pit-falls of Social Computing & Informatics in the Light of E-inclusion - Verdegem, Pieter (TripleC, 2010)
In this paper we reflect on how research and policies can and/or should help in the development of a sustainable information society for all. More specifically, we critically investigate how social computing & informatics can entail both potential and pitfalls, especially with regard to the difficult relationship between digital and social inclusion. First of all, traditional information society policies are scrutinized. Furthermore, we point at the existence of digital inequalities and we reflect briefly on policy intervention on this (e-inclusion). In addition, we also evaluate the raise of social computing & informatics. Finally, attention is given to the challenge of how research can contribute to the participation of all in the information society.